Current and future invasion of a predator with potential for impact negative in a region of high neotropical endemism - Iago V. Geller; Jean R. S. Vitule; João D. Ferraz; Alan D. Pereira; Mário L. Orsi (Neotropical Ichthyology)
Abstract The Neotropical region harbors the greatest fish diversity but has been experiencing a concerning decline. The Iguaçu basin, region of high endemism in southern Brazil, has extinction pressures due to the introduction of the non-native predator Salminus brasiliensis (dorado). It is believed that this species is increasing its occurrence, highlighting the need for assessments of its dispersal. This study aimed to update occurrence records of S. brasiliensis in the Iguaçu, evaluate its invasiveness and potential local extinctions and model its current and future distribution in southern Brazil. To achieve this, we employed citizen science, the Aquatic Species Invasiveness Screening Kit (AS-ISK), and ecological niche modeling. Results indicate a significant increase in S. brasiliensis occurrences between 2013 and 2024, with an upstream expansion of over 500 km. The AS-ISK classified the species as highly invasive (38/68), with a high-confidence protocol score. Species distribution modeling suggests a reduction in its native range in the Central-West region of Brazil, while its distribution is expanding into non-native areas in the South of the country. Although the species is iconic in South America, it poses a real threat to Iguaçu.